2021
DOI: 10.1002/14651858.cd013855
|View full text |Cite
|
Sign up to set email alerts
|

Transillumination and optical coherence tomography for the detection and diagnosis of enamel caries

Abstract: Waly 1995 {published data only} Waly NG. Evaluation of three diagnostic methods for initial proximal caries detection in primary molars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 127 publications
1
15
0
2
Order By: Relevance
“…OCT has clinical credibility of being a promising applications in a clinical detection and monitoring of early enamel caries (Jones et al, 2006; Kitasako et al, 2019). Moreover, OCT is expected to be a valuable tool for dentists and patients, providing non‐invasive and real time diagnostic information related to dental lesions and gaps in the context of operative and preventive treatments (Macey et al, 2021; Natsume et al, 2011; Sampaio et al, 2016). FD‐OCT could detect small enamel remineralization changes and there was a significant correlation between optical and mechanical findings (de Cara et al, 2012, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OCT has clinical credibility of being a promising applications in a clinical detection and monitoring of early enamel caries (Jones et al, 2006; Kitasako et al, 2019). Moreover, OCT is expected to be a valuable tool for dentists and patients, providing non‐invasive and real time diagnostic information related to dental lesions and gaps in the context of operative and preventive treatments (Macey et al, 2021; Natsume et al, 2011; Sampaio et al, 2016). FD‐OCT could detect small enamel remineralization changes and there was a significant correlation between optical and mechanical findings (de Cara et al, 2012, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, OCT is a no destruct promising technique to diagnose the first stage of caries disease allowing their clinical management and progression through the longitudinal evaluation of enamel demineralization (Kitasako et al, 2019; Macey et al, 2021). The technique is based in optical laws, where porous created in demineralized tissue increase the light scattering, causing changes on the optical properties of enamel during the decay process and allowing quantitative measurement of optical properties providing a repeatable means of tissue characterization (Jones & Fried, 2006; Kang, Darling, & Fried, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Lack of randomization may lead to the overestimation of the diagnostic study. To solve the problem of deficient randomization, some reviewers in dentistry suggested that the patient who needs tooth extraction can be randomized to be scanned by index test [41].…”
Section: Methodological Flaws and Risk Of Biasmentioning
confidence: 99%
“…As Macey et al reported, high-quality studies for DC could still be useful becausetheir true effect on the dental examination does not currently seem to have been explored. 26 To assess the performance of NIRLT in clinical setting, this prospective in vivo study aimed to investigate the validity of DC, ICDAS and BWR for detecting proximal caries on permanent teeth using histology as the gold standard. The hypothesis of the study was that DC performed better than BWR and ICDAS for detecting proximal caries.…”
Section: Introductionmentioning
confidence: 99%